2018
DOI: 10.1186/s13071-018-3222-9
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on the need and current status of efficient sex separation methods for mosquito genetic control

Abstract: Major efforts are currently underway to develop novel, complementary methods to combat mosquito-borne diseases. Mosquito genetic control strategies (GCSs) have become an increasingly important area of research on account of their species-specificity, track record in targeting agricultural insect pests, and their environmentally non-polluting nature. A number of programs targeting Aedes and Anopheles mosquitoes, vectors of human arboviruses and malaria respectively, are currently being developed or deployed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 48 publications
0
80
0
Order By: Relevance
“…Culicinae mosquitoes (including the genera Aedes and Culex) exhibit size sexual dimorphism as pupae. Consequently, Aedes mosquitoes have been, and are still, mechanically separated based on pupal size [15]. In Italy, a SIT trial to control Ae.…”
Section: Current Sex-sorting Status In Diptera Mass Releasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Culicinae mosquitoes (including the genera Aedes and Culex) exhibit size sexual dimorphism as pupae. Consequently, Aedes mosquitoes have been, and are still, mechanically separated based on pupal size [15]. In Italy, a SIT trial to control Ae.…”
Section: Current Sex-sorting Status In Diptera Mass Releasesmentioning
confidence: 99%
“…polynesiensis iv,v . In Anopheles mosquitoes, the current sex separation method is based on manual pupal identification, which allows sex-sorting of only 500 pupae per hour (reviewed in [15]). The working time is therefore very high, and the number of mosquitoes necessary for a program is difficult to reach.…”
Section: Current Sex-sorting Status In Diptera Mass Releasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive genetic and cytogenetic studies facilitated the development of a physical map of the medfly genome 8, . The annotated gene set provided opportunities for the identification of genes or loci-associated mutant phenotypes, such as the wp and tsl, used for the construction of GSS 16,17 . Salivary gland polytene chromosome maps developed for C. capitata, B. dorsalis, Z. cucurbitae, and B. tryoni show that their homologous chromosomes exhibit similar banding patterns.…”
Section: Mainmentioning
confidence: 99%
“…Coupling a Nix transgene with a conditional expression method (Fu et al, 2010), or a recently demonstrated gene drive strategy (Gantz et al, 2015;Kyrou et al, 2018) would enable the inheritance of the Nix transgene in almost all offspring, resulting in the removal or conversion of potentially all females. Such Nix transgenic lines that produce male-only progeny may be used as a population suppression method (Adelman and Tu, 2016) or to significantly reduce the cost and augment the scale of other mosquito control strategies that require the separation of males from females (Papathanos et al, 2018). The latest screening was done for G13 and G14 for N1 and N2 lines, respectively.…”
mentioning
confidence: 99%